Improving the clinical workflow of a MR-Linac by dosimetric evaluation of synthetic CT - Tang, Bin; Liu, Min; Wang, Bingjie; Diao, Peng; Li, Jie; Feng, Xi; Wu, Fan; Yao, Xinghong; Liao, Xiongfei; Hou, Qing; Orlandini, Lucia Clara (Frontiers in Oncology, 2022)
Adaptive radiotherapy performed on the daily magnetic resonance imaging (MRI) is an option to improve the treatment quality. In the adapt to shape (ATS) workflow of 1.5 T MR-Linac, the contours of structures are adjusted based on patient daily MRI and the adapted plan is recalculated on the MRI-based synthetic CT (syCT) generated by bulk density assignment. Since dosimetric accuracy of this strategy is a priority and requires evaluation, this study aims to explore the usefulness of adding an assessment of dosimetric errors associated with recalculation on syCT to the clinical workflow. Sixty-one patients, with various tumour sites, treated using a 1.5 T MR-Linac were included in this study. In Monaco V5.4, the target and organs at risk (OAR) were contoured, and a reference CT plan which contains information about the outlined contours, their average electron density (ED), as well as the priority of ED assignment, was generated. To evaluate the dosimetric error of syCT caused by the inherent approximation within bulk density assignment, the reference CT plan was recalculated on the syCT obtained from the reference CT by forcing all contoured structures to their mean ED defined on the reference plan. The dose-volume histogram (DVH) and dose distribution of the CT and syCT plan were compared. The causes of dosimetric discrepancies were investigated and the reference plan was reworked to minimize errors if needed. For 54 patients, gamma analysis of the dose distribution on syCT and CT show a the median pass rate of 99.7% and 98.5% with 3%/3 mm and 2%/2 mm criteria, respectively. DVH difference of targets and OARs remained less than 1.5% or 1 Gy. For the remaining patients, factors (i.e. inappropriate ED assignments) influenced the dosimetric agreement of the syCT vs CT reference DVH by up to 21%. The causes of the errors were promptly identified, and the DVH dosimetry was realigned except for two lung treatments for which a significant discrepancy remained. The recalculation on the syCT obtained from the planning CT is a powerful tool to assess and decrease the minimal error committed during the adaptive plan on the MRI-based syCT.